Diretrizes para elaboração de um instrumento para avaliação da sustentabilidade da Universidade Federal de Lavras - Valério, Gisele Aparecida (2021)
Sustainability is a complex concept, widely accepted and discussed, and involves the satisfaction of economic, environmental and social objectives, simultaneously, in all spheres and levels of society. Regarding the discussion on the role of Higher Education Institutions (HEI) to promote more sustainable development, it is observed that a new posture is required of these institutions in the face of the challenges to offer quality education, inserting the principles of sustainability in an interdisciplinary way in the educational process, as well as extending such knowledge to society. The general objective in this work is proposing guidelines that can contribute to the elaboration of an instrument for the sustainability evaluation of the actions developed at the Federal University of Lavras (UFLA). This research has an exploratory character, and is classified as quali-quantitative. The application of questionnaires, bibliographic research and documentary research were the techniques used for data collection. The results analysis was carried out through Content Analysis. With regard to sustainability in the institutional context of UFLA, it is clear that this term is strongly linked to the Institution's Environmental and Structuring Plan. It was found that many of the actions that were implemented at the beginning of the university's expansion process were incorporated into the routine of the academic community, as well as other initiatives that emerged in the meantime, and that they have shown positive results for the institution. As for the institution's commitment to sustainability, it is considered that this HEI recognizes its responsibility for promoting more sustainable development in the region and the country. However, a discourse more focused on environmental and economic sustainability is observed in several excerpts of the analyzed documents. With regard to the participants' perception regarding the sustainability of the actions developed in this HEI, there is a greater attention to issues related to the preservation of the natural resources of the campus. As for the institution's strengths, the participants highlighted the management of water resources, the management and treatment of chemical waste, among other environmental actions carried out at the institution. Regarding the institution's limitations, excessive paper consumption was the issue most addressed by the research participants. In terms of sustainability assessment, there is an absence of an assessment instrument that contemplates the main dimensions of an HEI in an integrated manner, and that meets the specificities of UFLA. Therefore, it is considered that the most appropriate way to assess the sustainability of the actions developed at UFLA is through an instrument that integrates the institution dimensions, and that is structured based on sustainability indicators appropriate to its reality. Among the contributions of literature to the development of an instrument for assessing sustainability in HEI, the following stand out: the importance of involving specialists from different areas, stakeholders, as well as the academic community in a democratic, participatory and transparent process; and the need for sustainability indicators to be adapted to the reality of each institution.